2021
DOI: 10.3390/su131910765
|View full text |Cite
|
Sign up to set email alerts
|

Revalorization of Pleurotus djamor Fungus Culture: Fungus-Derived Carbons for Supercapacitor Application

Abstract: Currently, there is increasing interest and effort directed to developing sustainable processes, including in waste management and energy production and storage, among others. In this research, corn cobs were used as a substrate for the cultivation of Pleurotus djamor, a suitable feedstock for the management of these agricultural residues. Revalorization of this fungus, as an environmentally friendly carbon precursor, was executed by taking advantage of the intrinsic characteristics of the fungus, such as its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Generally, this process leads to an increase in fixed carbon, ashes, and carbon content, with a decrease in volatile matter and oxygen content also occurring [11][12][13]. The vast majority of studies conducted on hydrochar generation found in existing literature are focused on aspects of bioenergy and chemistry [14,15], with very little information existing on the use of hydrochar in the agronomic field [16,17]. The use of spent coffee grounds (SCG) as an organic soil amendment has recently been studied due to their interesting macronutrient composition, of mainly lignin, cellulose, and hemicellulose, as well as their diverse array of mineral and bioactive compounds [18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this process leads to an increase in fixed carbon, ashes, and carbon content, with a decrease in volatile matter and oxygen content also occurring [11][12][13]. The vast majority of studies conducted on hydrochar generation found in existing literature are focused on aspects of bioenergy and chemistry [14,15], with very little information existing on the use of hydrochar in the agronomic field [16,17]. The use of spent coffee grounds (SCG) as an organic soil amendment has recently been studied due to their interesting macronutrient composition, of mainly lignin, cellulose, and hemicellulose, as well as their diverse array of mineral and bioactive compounds [18].…”
Section: Introductionmentioning
confidence: 99%